THE TRANINING OF INFORMATICS TEACHER'S IN ICT HISTORY - STOFFOVA, Veronika; STOFFA, Jan (Trends in education, 2008)
The study deals with the role of history of ICT and author's experience of its teaching in the training of informatics and ICT teacher's up to now. It shows that history is an organic part of the profile of science branches which create the theoretical and practical base of ICT ant that the knowledge of them should be considered to be a significant component of informatics literacy of ICT teacher's.
Keywords: History of ICT; informatics literacy; informatics and ICT teacher training